Trichoderma as a functional fungal group in the rhizosphere of maize and wheat under conservation and conventional agricultural practices - Ndaba, Nkosinathi Sthembiso (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc) -- Stellenbosch University, 2021.